The response of aluminium foams under quasi-static loading - Said, M. R. (2006)
Aluminium foams are now being considered for use in lightweight structural sandwich panels such as aircraft body and in energy absorption systems for protection from impacts. In both cases, they may be subject to uniaxial and as well as biaxial loadings. In this study, the uniaxial loading at a rate of 5 mm/min is perform to find the crushing characteristics and their directional dependency. Eight specimens are used in uniaxial compression. The load responses are recorded and compared with the biaxial loading. Biaxial tests are conducted in a custom testing facility between rigid platens, which can he moved independently in two principles direction at the same speed. Five specimens in biaxial loading in various densities are used. Considerable enhancement in collapse loads and lead to higher energy absorbtion is seen in biaxial loaded metallic foams in comparison with uniaxial loading. The refined empirical relationship for uniaxial loading is also developed and is satisfactory well in experiment